The Distributional Consequences of Real Exchange Rate Adjustment - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2003)
The paper focuses on distributional consequences of macroeconomic adjustment. The preferences of economic agents over the level of the real exchange rate derived from standard models are monotonic, with agents favoring either an infinitely appreciated or depreciated rate. To generate less extreme preferences, a model is presented where appreciation would depress economic activity, while a large depreciation would hit the tradable sector by limiting the availability of labor, offsetting the favorable price effect. The model is in the spirit of the dependent economy model, but built on explicit microfoundations. The results can be used to analyze political economy aspects of macroeconomic adjustment.